2012
DOI: 10.1007/s10107-012-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

A note on upper Lipschitz stability, error bounds, and critical multipliers for Lipschitz-continuous KKT systems

Abstract: We prove a new local upper Lipschitz stability result and the associated local error bound for solutions of parametric Karush-Kuhn-Tucker systems corresponding to variational problems with Lipschitzian base mappings and constraints possessing Lipschitzian derivatives, and without any constraint qualifications. This property is equivalent to the appropriately extended to this nonsmooth setting notion of noncriticality of the Lagrange multiplier associated to the primal solution, which is weaker than second-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…in contradiction with (26). Thus, the sequence {ξ j | j ∈ J} cannot have the zero accumulation point.…”
Section: ⊓ ⊔mentioning
confidence: 91%
See 1 more Smart Citation
“…in contradiction with (26). Thus, the sequence {ξ j | j ∈ J} cannot have the zero accumulation point.…”
Section: ⊓ ⊔mentioning
confidence: 91%
“…In fact, this error bound is equivalent to the assumption that the multiplier (λ,μ) ∈ M(x) is noncritical, as defined in [30]; see also [26] and [31,Section 1.3]. As in what follows we would only invoke this notion for the equality-constrained case, we give here the corresponding simpler definition.…”
Section: Introductionmentioning
confidence: 98%
“…In the terminology of [21, Definition 1.41] (see also [19,15]), a multiplier λ * associated to a primal solution x * of the KKT system (6.1), is called noncritical if there exists no pair (ξ, η) ∈ R n × R m , with ξ = 0, satisfying (6.4)…”
Section: Individual Error Bounds For Active Pieces In Case Of Complemmentioning
confidence: 99%
“…It can be easily shown that if SOC (6.3) holds, then λ * is automatically noncritical; see [19,15,21] for details. Also, it should be emphasized that usually, the class of noncritical multipliers is much wider than the class of multipliers satisfying SOC.…”
Section: Individual Error Bounds For Active Pieces In Case Of Complemmentioning
confidence: 99%
See 1 more Smart Citation